2012
DOI: 10.1177/1745691612462586
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding Replications

Abstract: Although replications are vital to scientific progress, psychologists rarely engage in systematic replication efforts. In this article, we consider psychologists' narrative approach to scientific publications as an underlying reason for this neglect and propose an incentive structure for replications within psychology. First, researchers need accessible outlets for publishing replications. To accomplish this, psychology journals could publish replication reports in files that are electronically linked to repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(97 citation statements)
references
References 32 publications
1
87
0
1
Order By: Relevance
“…Inviting the initial author to review replication studies can help reduce this, and (in the case of a Registered Report) the initial authors can be invited to provide a Stage 1 review before data collection (see Marsden, Morgan-Short, Trofimovich, & Ellis, 2018). Even more transparent practices that may promote more and higher quality replication, reduce publication bias, and reduce perceptions of bullying include (a) publishing open reviews and authors' responses to reviews (e.g., in BMC Psychology; Laws, 2016); (b) giving initial authors an automatic right to a peer-reviewed published commentary (e.g., in Perspectives in Psychological Science; in our sample, we found one such example, Kanno, 2000); and (c) adversarial collaborations (Coyne, 2016;Kahneman, 2014;Koole & Lakens, 2012;Mellers, Hertwig, & Kahneman, 2001), where researchers who account for phenomena differently agree to work together following a single protocol. We raise awareness of the existence of these more extreme measures but hope that the other mechanisms that we recommend, such as transparent materials and data and the reviewing of methods prior to data collection, serve to reduce any perception of bullying that independent replication may engender.…”
Section: Independence Combined With Professional Practice and Collegimentioning
confidence: 76%
See 2 more Smart Citations
“…Inviting the initial author to review replication studies can help reduce this, and (in the case of a Registered Report) the initial authors can be invited to provide a Stage 1 review before data collection (see Marsden, Morgan-Short, Trofimovich, & Ellis, 2018). Even more transparent practices that may promote more and higher quality replication, reduce publication bias, and reduce perceptions of bullying include (a) publishing open reviews and authors' responses to reviews (e.g., in BMC Psychology; Laws, 2016); (b) giving initial authors an automatic right to a peer-reviewed published commentary (e.g., in Perspectives in Psychological Science; in our sample, we found one such example, Kanno, 2000); and (c) adversarial collaborations (Coyne, 2016;Kahneman, 2014;Koole & Lakens, 2012;Mellers, Hertwig, & Kahneman, 2001), where researchers who account for phenomena differently agree to work together following a single protocol. We raise awareness of the existence of these more extreme measures but hope that the other mechanisms that we recommend, such as transparent materials and data and the reviewing of methods prior to data collection, serve to reduce any perception of bullying that independent replication may engender.…”
Section: Independence Combined With Professional Practice and Collegimentioning
confidence: 76%
“…In psychology, Makel et al (2012) found 91.7% supported initial findings when there was author overlap, versus 64.6% when there was no overlap. Given the high rate of reproducibility with author overlap, Koole and Lakens (2012) focused only on independent replications in their set of recommendations for replication, arguing that "the most compelling direct replications are conducted independently by different researchers than the original study" (p. 609). This was a key motivator for the preregistered multisite replications published by and Practices in Psychological Science), in which research teams all have access to the same materials but conduct the study independently (and in some cases, do not look at the data until they have been passed to the replication convener or coordinating editor).…”
Section: Extent Of Reproducibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…3 Scientists across numerous disciplines have expressed serious concerns and engaged in both philosophical and practical discussions about reproducible research. Disciplines represented in these discussions include biology, 4 biomedical 5 and preclinical research, 6,7 business and organizational studies, [8][9][10][11][12] computational sciences, 13,14 drug discovery, 15 economics, 16,17 education, [18][19][20][21][22] epidemiology and statistics, [23][24][25] genetics, 26 immunology, 27 policy research, 28 political science, [29][30][31][32][33][34][35][36] psychology, 29,[37][38][39][40][41][42][43] and sociology. 44 As a case in point: research indicates that more than half of psychology studies fail reproducibility tests.…”
Section: Background and Contextmentioning
confidence: 99%
“…This emphasizes the importance of independent replications; an appeal that has been made repeatedly in recent years to ensure the self-correcting nature of psychological science (e.g. Asendorpf et al, 2013; Koole & Lakens, 2012; Makel, Plucker, & Hegarty, 2012; Nosek, Spies, & Motyl, 2012; Pashler & Wagenmakers, 2012). In this spirit, we attempted to replicate Wichert et al’s (experiment 1, 2013a) findings using similar procedures, manipulation, measures, and population.…”
mentioning
confidence: 99%